PENGARUH KOMPETENSI PROFESIONAL GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DI SD NEDERI NO. 12 PULAU PAMALIKANG DESA SABARU KECAMATAN LIUKANG KALMAS KABUPATEN PANGKAJENE DAN KEPULAUAN - M, Masmur (Universitas Islam Negeri Alauddin Makassar, 2020)
The objectives of this study were 1) To determine the effect of teacher professional competence on student learning outcomes in grade V at SD Negeri No. 12 Pamalikang Island Sabaru Village, Pangkajene Regency and Archipelago. 2) To determine the effect of student motivation on learning outcomes of class V students at SD Negeri No. 12 Pamalikang Island, Sabaru Village, Liukang Kalmas District, Pangkajene Regency and the Archipelago. 3) To determine the effect of teacher professional competence and student learning motivation together on the learning outcomes of fifth grade students at SD Negeri No. 12 Pamalikang Island Sabaru Village, Pangkajene Regency and Archipelago. The type of research used is correlational quantitative which aims to determine whether or not there is an influence between the two variables to be measured. Total population of 38 students consisted of class III to class V SD Negeri No.12 Pamalikang Island. The sampling technique used was saturated / census samples.Based on the results of the study showed that 1) the professional competence of teachers has a positive and significant effect on student learning outcomes in Islamic Education subjects at SD Negeri No. 12 Pamalikang Island, Sabaru Village, Liukang Kalmas District, Pangkajene Regency and the Archipelago. 2) Learning motivation has a positive and significant effect on student learning outcomes in Islamic Education subjects at SD Negeri No. 12 Pamalikang Island, Sabaru Village, Liukang Kalmas District, Pangkajene Regency and the Archipelago. 3) Teacher professional competence and learning motivation simultaneously have a positive and significant effect on student learning outcomes in Islamic Education subjects at SD Negeri No. 12 Pamalikang Island, Sabaru Village, Liukang Kalmas District, Pangkajene Regency and the Archipelago